The Scope of Reasonable Suspicion in the National Criminal Procedure - Andrei Pântea (Journal of Danubian Studies and Research, 2020)
Currently, there is no scientific consensus where the place of reasonable suspicion is in the legal framework of criminal proceedings. Although there is a legal regulation of reasonable suspicion in the criminal procedure code provided at general terms and definitions, and despite repeated references to the concept, the debates on the topic continue. It is not possible to talk about the legal regulation and the quality of relationships related to the implementation of the studied concept, if so far the academia and professionals did not developed a unified or at least a majority approach to what is a reasonable suspicion and what is its scope.